Olfactory Dysfunction and Its Relationship With Clinical Features of Parkinson's Disease - Zhou, Yangjie; He, Runcheng; Zhao, Yuwen; He, Yan; Hu, Yacen; Sun, Qiying; Xu, Qian; Tan, Jieqiong; Yan, Xinxiang; Tang, Beisha; Guo, Jifeng (Frontiers in Neurology, 2020)
Objective: To conduct an investigation into the reliability of assessing olfactory function of patients with PD by hyposmia rating scale (HRS) in China and compare other non-motor features between patients with PD with olfactory dysfunction (PD-OD) and patients with PD without olfactory dysfunction (PD-NOD) according to the result of olfactory function appraised by Sniffin’ Sticks test. Methods: A total of 320 patients with clinically confirmed or clinically possible PD were recruited. Assess olfactory function of all participants with HRS and the Sniffin’ Sticks test. Collect demographic data and clinical information, and patients were evaluated using standardized assessment protocols. With reference to the Sniffin’ Sticks test, compute the specificity, sensitivity, coincidence rate and Kappa value of HRS, then evaluate its reliability. We divided patients into PD-OD and PD-NOD groups based on the result of olfactory function assessed by Sniffin’ Sticks test. Clinical manifestations were compared between PD-OD and PD-NOD. Results: The frequency of OD evaluated by the Sniffin’ Sticks test was 65.6%, while the percentage of OD was 55.6% when using HRS measured olfactory function. Referring to the Sniffin’ Sticks test, the specificity, sensitivity, coincidence rate and Kappa value of HRS were 82.73%, 75.71%, 78.13% and 0.55, respectively. The area under ROC curve (AUC) of HRS was 0.793.There was no difference in demographic information between PD-OD and PD-NOD. Patients with hyposmia had more severe non-motor symptoms. Conclusion: HRS is of great value as a self-assessment scale for evaluating olfactory function, especially in PD patients over 55. Moreover, PD patients with hyposmia have more severe non-motor features than PD patients without hyposmia, mainly in terms of mood and constipation.